Impact and Influence of Early Marriage Cultural Traditions - Arikarani, Yesi; Mahersal, Yonas (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
The focus of this research is the rampant phenomenon of early marriage, which causes cultural shifts. The cultural tadisi of society has a tendency to marry at an early age to cause impact and influence. The research approach used is qualitative, with in-depth interview data collection techniques, observation, and documentation. The results showed that early marriage in Mardiharjo village has many effects on biological and psychological human resources, education, reproductive health, the economy, divorce, social media, religion, and the economy. Early marriage has a negative effect on families because they are not mentally prepared and do not have independence. Deviant behavior such as free sex and pregnancy outside marriage is caused by environmental factors and dating trends. Underage marriages are permitted by the local government's religious administration office on condition that they go through a religious court decision.